Pendampingan Pembuatan Proposal Riset Menuju LKIR di MAN 2 Kota Probolinggo - Dyah Ariyanti; Hermin Arista; Ary Analisa Rahma; Indro Wicaksono; Linda Kurnia Supraptiningsih; Ira Aprilia; Dwi Putri Kartini (Universitas Pahlawan Tuanku Tambusai, 2022)
The purpose of this community service activity is to provide assistance in making research proposals for scientific papers that will be included in the MYRES competition. The research proposals that have been collected will be selected based on several components, such as aspects of the originality of the idea, the novelty of the idea, the relevance of the theory and theoretical studies used, research methods, benefits for the wider community, as well as coherence and writing techniques. The method of implementing this community service activity is advocacy, which consists of the stages of planning, implementing and evaluating. There are three areas of research, namely the field of mathematical science and technology development; social and humanitarian spheres (social and humanities); and the field of religious science. Based on the evaluation of the implementation results, from 11 classes, 115 proposal titles were collected submitted by the group of students who were prospective participants in the competition and will be selected into the best 40 to be included in the competition. Furthermore, the team selected the proposal into 6 best titles that will be funded by madrasahs as a product of research including the best 2 each in each field of MYRES.